A Survey On Physical Activity Monitoring (PAM) Among Malaysian Young Adults - Rajkumar Krishnan Vasanthi; Kishanthini Murugayah; Praveen Jayaprabha Surendran; Ali Md Nadzalan; Vinosh Kumar Purushothaman; Yughdtheswari Muniandy; Sivabavani Sadasivam (Medsci Publications, 2024)
Background: Physical Activity Monitoring (PAM) is used effectively to encourage and promote an increased level of Physical Activity (PA) in young adults. The aim of this study was to determine the status of PAM and to identify the type of monitoring method being used among young adults in Malaysia is avoid health risks. Methods: In this cross-sectional study, the data collection was based on a validated customized questionnaire carried out by sending it online via email, WhatsApp, and Facebook with an explanation of the research background, including the link of the survey questionnaires to the respondents. Results: A total of 400 participants completed this survey and most participants were in the age range between 25-29 and 50.7% were males. Nearly half of the participants (61.0%) declared that they were monitoring their PA regularly and smartwatches (20.5%) are the most preferable type for PAM. Conclusion: In this survey, it can be concluded that more awareness needs to be created on the importance of PAM among young adults as nearly another half of the participants surveyed that they were not monitoring their regular PA to follow a healthy lifestyle.